2021
DOI: 10.1155/2021/7853335
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0001658 Inhibits Intervertebral Disc Degeneration Development by Regulating hsa-miR-181c-5p/FAS

Abstract: Background and Purpose. Intervertebral disc degeneration (IDD) is the main cause of low back pain, but its pathogenesis has not been studied clearly. Circular RNA is a type of noncoding RNA (ncRNA). In this study, we studied the potential role of circular RNA in the pathogenesis of IDD. Methods. We obtained microarray data (GSE116726, GSE67566) from Gene Expression Omnibus database, and differential expression level of ncRNA in nucleus pulposus (NP) tissues of IDD patients was analyzed. The potential circRNA-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…LINC01359 may be linked to hepatocellular carcinoma (HCC), that's all we got (Tan et al, 2019). LUCAT1 is not available in PubMed, but the silencing of hsa-miR-181c-5p can inhibit the proliferation and promote the apoptosis of nucleus pulposus cells (Meng and Xu, 2021). We revealed a direct association between these four key lncRNAs and IDD, it may be important for the pathogenesis and clinical treatment exploration of IDD, which will be our focus in the future.…”
Section: Discussionmentioning
confidence: 88%
“…LINC01359 may be linked to hepatocellular carcinoma (HCC), that's all we got (Tan et al, 2019). LUCAT1 is not available in PubMed, but the silencing of hsa-miR-181c-5p can inhibit the proliferation and promote the apoptosis of nucleus pulposus cells (Meng and Xu, 2021). We revealed a direct association between these four key lncRNAs and IDD, it may be important for the pathogenesis and clinical treatment exploration of IDD, which will be our focus in the future.…”
Section: Discussionmentioning
confidence: 88%
“…Apoptosis was the first type of RCD to be identified [ 85 ]. Sixteen circRNAs have been reported to regulate NPCs apoptosis, including nine circRNAs that were shown to promote NPCs apoptosis (circ_0004354 [ 63 ], circ_0040039 [ 63 ], circITCH [ 64 ], circ_0083756 [ 65 ], circRNA_0000253 [ 67 ], circ_001653 [ 69 ], circRNA_104670 [ 70 ], circ_RERE [ 87 ], and circ_0001658 [ 88 ]) and seven circRNAs that were shown to inhibit NPCs apoptosis (circGLCE [ 76 ], circRNA VMA21 [ 77 ], circ- GRB10 [ 78 , 79 ], circRNA-CIDN [ 80 ], circERCC2 [ 81 ], circARL15 [ 89 ], and circ_0059955 [ 90 ]) ( Table 1 and Fig. 2 ).…”
Section: Regulatory Role Of Circrnas In Degeneration Of Nucleus Pulposusmentioning
confidence: 99%
“…Wang et al ( 88 ) reported that circ_0001658 is significantly upregulated in osteosarcoma tissue and increases proliferation, migration and invasion of osteosarcoma cells and suppresses apoptosis by targeting the miR-382-5p/YB-1 signaling pathway. Meng and Xu ( 89 ) found that circ_0001658 expression is significantly increased in the NP tissue obtained from patients with IDD and hsa-miR-181c-5p is downregulated. In addition, they revealed that circ_0001658 upregulation suppressed proliferation of NP cells and increased apoptosis.…”
Section: Ncrnas In Autophagy and Apoptosismentioning
confidence: 99%